Strategic Planning Process applied to the Greek professional sport clubs - Θεάκου, Έλενα (Πανεπιστήμιο Πελοποννήσου, 2016)
The primary purposes of this study were: (1) to determine the extent to which the strategic planning process is being used in the Greek professional sport sector (football and basketball clubs), (2) to identify the key factors that discourage the Greek professional sport clubs from engaging in strategic planning activities, (3) to identify the main similarities and key differences between the two samples and (4) to examine the relationship between the levels of planning and selected variables: (a) type of sport club (football versus basketball), (b) managers’ educational background and (c) managers’ work experience. The questionnaire instrument was developed by the researcher based on the reviewed literature on strategic planning as well as on input and suggestions from reviews offered by a selected panel of experts. Thirty professional sport clubs (football and basketball clubs), which had continuous attendance in the first division of Greek Championships (Super league and A1, respectively) during three consecutive years (from 2011 to 2013), were surveyed. Responses were received from all of the professional sport clubs with a response rate of 82,2%. The findings of the study revealed that the strategic planning process is applied to a little extent, as only the 26,4% of the Greek professional sport clubs were identified as strategic planners. Moreover, professional sport clubs need to invest more on strategies that play an important role on organization’s success.
Στρατηγικός Σχεδιασμός στον Ελληνικό Επαγγελματικό Αθλητισμό
Keywords: Professional sports - Management; Professional sports - Strategic planning; Επαγγελματικός αθλητισμός - Διοίκηση και οργάνωση; Επαγγελματικός αθλητισμός - Στρατηγικός σχεδιασμός; Strategic planning; Professional sport clubs; Στρατηγικός σχεδιασμός; Επαγγελματικός αθλητισμός